CoMET: a protocol for a randomised controlled trial of co-commencement of METformin as an adjunctive treatment to attenuate weight gain and metabolic syndrome in patients with schizophrenia newly commenced on clozapine. Issue 3 (2nd March 2018) - Siskind, Dan; Friend, Nadia; Russell, Anthony; McGrath, John J; Lim, Carmen; Patterson, Sue; Flaws, Dylan; Stedman, Terry; Moudgil, Vikas; Sardinha, Savio; Suetani, Shuichi; Kisely, Steve; et al.
Abstract : Introduction: Clozapine, while effective in treatment refractory schizophrenia, is associated with significant weight gain, heart disease and increased risk of type 2 diabetes mellitus (T2DM). Although there is evidence for weight loss with metformin for people with obesity who are already taking clozapine, there have been no published trials that have investigated the effect of metformin in attenuating weight gain at the time of clozapine initiation. Methods and analysis: A 24-week double-blind placebo-controlled trial of concomitant prescription of metformin at clozapine commencement. Eighty-six people being commenced on clozapine will be randomised to placebo or metformin (variable dose, up to 2 g/day). The primary outcome is comparative end point body weight, between the placebo and metformin groups. Secondary outcomes are comparative rates of conversion to T2DM, alteration of metabolic syndrome parameters, proportion gaining >5% body weight and changes in diet and appetite. We will additionally examine biomarkers associated with change in weight among trial participants. Ethics and dissemination: Ethics approval was granted by the Metro South Human Research Ethics Committee HREC/17/QPAH/538-SSA/17/QPAH/565. We plan to submit a manuscript of the results to a peer-reviewed journal, and present results at conferences, consumer forums and hospital grand rounds. Trial registration number: ACTRN12617001547336; Pre-results.